(untitled) (Faculty of Education Scientific Journal, 2023)
Teaching English language skills to the students since the time they are introduced to study English as a subject in their curriculum at schools is an important area of concern in Libya. The main objective of this paper is to suggest the effective ways to teach English language skills at the secondary school level in Libya. This study is conducted at the secondary school located in Brack town in Wadi Alshatti region in Libya. The students are given a questionnaire for their feedback regarding the way they are taught different areas of English language like vocabulary, grammar, listening, speaking by their teachers and a few oral questions are also asked to just guess the English language skills of the students. Finally, the paper presents the findings and recommendations. Lack of enough vocabulary and knowledge of grammar are seen as the main factors crippling the English language learning skills among the learners.